2018
DOI: 10.18800/psico.201802.003
|View full text |Cite
|
Sign up to set email alerts
|

Autoconcepto profesional: Predicción del compromiso con el trabajo en equipo

Abstract: The role of self-concept in the context of the way in which work teams function has not been clearly identified, demonstrating the importance of studying this phenomenon. The objective was to evaluate the explanatory power of professional self-concept and personal beliefs in relation to affective commitment. The study was performed with data from 405 Brazilian employees, using a questionnaire with satisfactory reliability indices (α between .75 and .91). The results showed a significant influence of self-conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Some past studies were conducted using the scale, and the Cronbach's alpha values were found to be 0.76 (Palacios and Souza, 2018) and 0.72 (Puggina et al. , 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some past studies were conducted using the scale, and the Cronbach's alpha values were found to be 0.76 (Palacios and Souza, 2018) and 0.72 (Puggina et al. , 2015).…”
Section: Methodsmentioning
confidence: 99%
“…It can be further evaluated by the employee's ability to perform the tasks assigned, the level of self-confidence and the satisfaction one derives from the successful completion of jobs given. Satisfaction is a crucial predictor of self-concept because employees who experienced satisfaction with accomplishing the tasks regarded themselves as content and capable (Palacios and Souza, 2018; Souza and Palacios, 2011) and also committed (Tamayo et al. , 2001).…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…Schlegel et al (2011) conceived self-concept as a reflection of one's desires and is impacted by conditions of self-worth. The self-concept plays a pivotal role in organizational psychology: a positive self-concept generates team interaction, worker motivation, commitment (Allameh et al, 2012), Personal characteristics are fundamental to understanding human behavior in the workplace (Puente-Palacios and De Souza, 2018). The self-concept is one of the dimensions of individual characteristics.…”
Section: Self-conceptmentioning
confidence: 99%
“…This concept has recently received some attention as a structural theoretical construct among many professional sectors [ 23 ]. Despite this, through a preliminary search in MEDLINE, the Cochrane Database of Systematic Reviews, and JBI Evidence Synthesis, it was possible to verify that this topic has been almost unstudied, and there is no current or review currently underway about it.…”
Section: Introductionmentioning
confidence: 99%